Sistema eletrohidráulico para acionamento da esteira vibratória do arrancador-invertedor de amendoim - Ferezin, Evaldo [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The peanut harvest is a critical operation, which suffer the greatest productivity losses, and should be completed in the shortest time possible, to minimize other losses that result from adverse climatic conditions. Taking these factors into consideration and also that the digger manufacturers indicate that the equipment should work with the power take-off rotation (PTO) below the limit established by the technical standards for agricultural machinery (540 rpm). This work aimed to develop a system to transmit different rotations to the digger, with independent adjustment of the rotation of the PTO and the displacement speed used in the tractor, and analyze the performance of the mechanized set of digging before and after the change of equipment. The work was conducted in the agricultural years of 2011/2012 and 2013/2014 in the Experimental Farm area of Education Research and Production of UNESP / FCAV, Jaboticabal, state of São Paulo, located in geodetic coordinates: latitude 21 ° 14 'S and longi tude 48 ° 16 'W, with an average altitude of 560 m, average slope 4% and Aw climate (subtropical). The soil of the area is classified as Oxissoil and the soil tillage was conventionally. Peanut seeds were used (Arachis hypogea L.) cultivar Runner IAC 886. The system developed to change the shaking conveyor rotation was electrohidraulic, triggered by the auxiliary hydraulic system (remote control) and controlled by the operator. Initially the equipment was evaluated at the recommended conditions marketed, with banded design, with rotations of 85, 100, 114, 127 and 142 rpm in the digger shaking conveyor. The second experiment, done with the starter-Flipping using the electrohydraulic system for controlling the rotation of the digger shaking conveyor, also with banded design, with 5 rotations (80, 90, 100, 110 and 120 rpm) and three travel speeds mechanized assembly (3.5; 4.2 and 5.0 km h-1). The machine can work with travel speed ...

A colheita do amendoim é uma operação crítica, onde ocorrem as maiores perdas de produtividade, e devendo ser finalizada no menor tempo possível, para minimizar outras perdas que são decorrentes de fatores climáticos adversos. Levando-se em consideração esses fatores e também que os fabricantes de arrancadores-invertedores indicam que o equipamento deve trabalhar com a rotação da tomada de potência (TDP) abaixo do limite estabelecido pelas normas técnicas para máquinas agrícolas (540 rpm). Este trabalho teve o objetivo de desenvolver um sistema que transmita diferentes rotações de trabalho para o arrancador-invertedor, com regulagem independente da rotação da TDP e da velocidade utilizada no trator, bem como analisar o desempenho do conjunto mecanizado de arranquio antes e após a alteração do equipamento. O trabalho foi conduzido nos anos agrícolas de 2011/2012 e 2013/2014 em área experimental da Fazenda de Ensino Pesquisa e Produção da UNESP/FCAV, Jaboticabal, no estado de São Paulo, localizada nas coordenadas geodésicas: latitude 21°14' S e longitu de 48°16' W, com altitude média de 560 m, declividade média 4% e clima Aw (subtropical). O solo da área experimental é classificado como LATOSSOLO VERMELHO Eutroférrico típico e foi preparado de forma convencional. Foram utilizadas sementes de amendoim (Arachis hypogea L.) cultivar Runner IAC 886. O sistema desenvolvido para alterar a rotação da esteira vibratória foi eletrohidráulico, acionado pelo sistema hidráulico auxiliar (controle remoto) e controlado pelo operador. Inicialmente o equipamento foi avaliado nas condições preconizadas comercialmente, com delineamento em faixas, com rotações de 85, 100, 114, 127 e 142 rpm no eixo da esteira vibratória. O segundo experimento, feito com o arrancador-invertedor utilizando o sistema eletrohidráulico para controle da rotação da esteira vibratória, também com delineamento em faixas, com...
Keywords: Amendoim; Amendoim - Colheita; Mecanização agrícola; Máquinas agrícolas; Perdas durante a colheita; Farm mechanization